Consumer's Perception of Brand Loyalty in Car Choices - Hassanzade, Mohammadreza (Eastern Mediterranean University (EMU) - Doğu Akdeniz Üniversitesi (DAÜ), 2019)
This thesis empirically investigates the customer's perceptions of brand loyalty in car buying decisions along with other different variables that can affect this process. A total number of two hundred fifty people were selected from different geographic areas in North Cyprus and participants filled a hundred and sixty questionnaires. Independent t-test, descriptive Statistics, one-way analysis of variance (ANOVA) and analysis of regression were employed to examine the relevant subject. Results of independent T-test exposed the presence of statistically significant differences among men and women are based on ‘willingness to pay extra costs for making capable this brand in contest with other brands’, ‘Other brands activities do not affect me in buying this brand’ ‘For solving troubles I can trust to Benz or BMW’ and ‘Never get disappointed by Benz or BMW’. To examine the probability of having to some extent potential differences among the perceptions of the respondents' subset groups, status and income level, Analysis of Variance (ANOVA) test was conducted. ANOVA test results revealed that ‘the advertisement and promotion of the brand have good results’ and "Best experiences will rise as I buy this brand" showed statistical significant differences based on job status whereas ‘Never get disappointed by Benz or BMW’ and ‘My satisfaction is secured by Benz or BMW’ showed significant differences based on income level. Finally, the regression results showed that there is a positive significant relationship between brand loyalty and its determinants. Keywords: Brand Loyalty, Brand Trust, Service Quality, Brand Communication, BMW, Mercedes Benz, North Cyprus, Independent T-test, Anova Test, Regression Analysis.

ÖZ: Bu tez, araç satın alma kararında marka sadakati ile ilgili müşteri algılarını ilgili süreçte etkili olabilecek farklı değişkenlerle ampirik olarak incelemektedir. Kuzey Kıbrıs'taki farklı coğrafi bölgelerden toplamda yüz elli kişinin seçildiği yüz altmış kişinin anketi doldurduğu belirlenmiştir. Tanımlayıcı İstatistikler, Bağımsız t-testi, tek yönlü varyans analizi (ANOVA) ve regresyon analizi, ilgili olayı incelemek için kullanılmıştır. T-analizi, marka sadakatine ilişkin cinsiyet algısı arasında istatistiksel olarak anlamlı farklılıklar gözlemlendiğini belirtir. Diğer markalarla rekabet halinde bu markayı yapabilmek için ekstra maliyetler ödemeye istekli', 'Diğer marka etkinlikleri bu markayı satın almamı etkilemiyor', ‘sıkıntıları çözme Benz veya BMW'ye güvenmeden geçer’ ve 'Benz veya BMW tarafından asla hayal kırıklığına uğratılmazsınız' gibi faktörler için kadın ve erkek arasında farklılıklar oluşmaktadır. Ankete katılan alt grupların, iş durumu ve gelir düzeyine göre algıları arasında herhangi bir potansiyel farklılığın bulunma olasılığını incelemek için Varyans Analizi (ANOVA Testi) yapılmıştır. Anova test sonuçları, “markanın reklamının ve tanıtımının iyi sonuçlar verdiğini” ve “bu markayı satın alırken en iyi deneyimlerin yükseleceği” faktörleri iş durumuna göre istatistiksel olarak anlamlı farklılıklar belirtmiştir. Ayni zamanda “Benz veya BMW tarafından asla hayal kırıklığına uğratılmamış” ve 'Benim memnuniyetim Benz veya BMW tarafından güvence altına alınmıştır', gibi faktörlerde gelir düzeyine göre önemli farklılıklar göstermiştir. Son olarak, regresyon sonuçları, marka sadakati ve belirleyicileri arasında pozitif anlamlı bir etkiye sahip olduğunu göstermektedir. Anahtar Kelimeler: Marka Sadakati, Marka Güveni, Hizmet Kalitesi, Marka İletişimi, BMW, Mercedes Benz, Kuzey Kıbrıs, Bağımsız T-testi, Anova Testi Regrasyon Analizi
Master of Arts in Marketing Management. Thesis (M.A.)--Eastern Mediterranean University, Faculty of Business and Economics, Dept. of Business Administration, 2019. Supervisor: Prof. Dr. Sami Fethi
Keywords: Business Administration; Marketing Management; Brand loyalty--Brand choice--Car Brands--Car Buying--Cyprus (Turkish Republic of Northern Cyprus, 1983-); Customer satisfaction, Brand loyalty; Brand Loyalty; Brand Trust; Service Quality; Brand Communication; BMW; Mercedes Benz; North Cyprus; Independent T-test; Anova Test; Regression Analysis